Educação em direitos humanos e justiça restaurativa: cruzamentos paradigmáticos de reforma da justiça criminal. - Teófilo, Anna Mayra Araújo (2015)
In contemporary Brazil, changes in the population dynamics reveals the increase of the crime and indicates the necessity of rethink, lato sensu, the criminal models adopted by states in their various spheres, skills. In this sense, it has proved crucial to the formulation of a new model of criminal justice that takes into account the new parameters of a newly formed democratic society. In other words, it is essential to think in new criminal legal phenomena that have as their primary care the respect for human rights and, consequently, the dignity of the human person during the resolution pf conflicts related to criminal harvest. The objective of this research it is to reveal the compatibility that education on human rights and restorative justice present in the humanization of the criminal justice process. Therefore, this work will build in the researches, among other authors, of Bitencourt, about the decay of the prison system; Neves, Van Ness, Pallamolla with respect to restorative justice; and, finally, Reardon, Bobbio and Boiteux in human rights education as a practice model of education for peace. In methodological terms, the research realized it was of bibliographic nature, with a literature review of the issues involved for its. At the end of the survey it was found the hypothesis which suggests that to practice a humanizing criminal justice, arising from the principle of moral and material solidarity, it is necessary to reform the current criminal justice from encouraging human rights education and the effective consolidation of restorative justice within the Brazilian legal system. This research is relevant not only because of the lack of the subject from standpoint of international law as well because the fact of the thematic still be motive of large differences in harvest of contemporary International Relations.